GRI Index FY13 - World Bank (Washington, DC, 2015)
The annual global reporting initiative (GRI) update encompasses global World Bank lending operations as well as its corporate operations. Corporate operations refer to International Bank of Reconstruction and Development (IBRD), International Development Association (IDA), Multilateral Investment Guarantee Agency (MIGA), and Global Environment Facility (GEF) secretariat staff as well as the buildings that house staff members. GRI indicators for environment, apply primarily to performance of Washington, District of Columbia (D.C.) facilities (which house 60 percent of WB staff) with country office data noted, when relevant. The WB reports on a fiscal year basis, which extends from July 1 through June 30. This report covers FY 2013 (July 1, 2012 - June 30, 2013).